2015
DOI: 10.2147/jpr.s85741
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a pain self-management intervention combining written and video elements on health-related quality of life among people with different levels of education

Abstract: Abstract:Combining written and video material could increase the impact of health education for people with less education, but more evidence is needed about the impact of combined materials in different formats, especially in the context of chronic pain self-management. This study tested the impact of combining written information about self-managing chronic joint pain, which used language at a high reading level, with a DVD containing narrative video material presented directly by patients, using language at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…The study by Baraz- Pardenjani et al in Iran showed that the use of video education in hemodialysis patients increased the overall quality of life and also increased the bodily functioning, mechanical function, mental role, social functioning and common health ideas [ 23 ]. A research by Stalker in the United Kingdom indicated that the use of video education in hemophilia patients with different educational background increased the overall quality of life, mental and physical concepts [ 34 , 35 ]. The finding in this study was in accordance with the studies mentioned earlier.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Baraz- Pardenjani et al in Iran showed that the use of video education in hemodialysis patients increased the overall quality of life and also increased the bodily functioning, mechanical function, mental role, social functioning and common health ideas [ 23 ]. A research by Stalker in the United Kingdom indicated that the use of video education in hemophilia patients with different educational background increased the overall quality of life, mental and physical concepts [ 34 , 35 ]. The finding in this study was in accordance with the studies mentioned earlier.…”
Section: Discussionmentioning
confidence: 99%
“…These results highlight the very significant public health potential of carefully designed and administered Internet-delivered pain management programs and indicate that these programs can be successfully administered with several levels of clinical support. Evidence also suggests that combining high-reading level written material with more accessible video material can improve its impact among patients with less education [ 58 ].…”
Section: Discussionmentioning
confidence: 99%